Epidemiological Correlation Between Her-2 Expression With Histological Type and Grade Breast Carcinoma On Oncology Department, Moewardi Hospital, Surakarta, Indonesia - Dian Ibnu Wahid; Widyanti Soewoto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Some woman have breast tumors with higher level of HER-2. HER-2 receptor is is a member of the epidermal growth factor receptor family which one such gene that can play a role in the development of breast carcinoma. Normally, HER-2 receptors control breast cell grows, divides, and repair breast cell. But in pathologic conditions it make too many copies. The aim of this study  was to evaluated the expression of HER-2 in woman breast carcinoma and to compare it with Histological Type and Grade. We Observed  1.395 patients with breast carcinoma. The mean age of the patients was 45.7 (Ranged 23-73 years). In this group the frequency of Her2 positive was higher than other. The incidence of patients above 50 years of age were significancy higher in Her2 positive with 363 (47%). For tumor grading, the highest on G3 with the results 764 (54.7%). G3 got the highest results on Her2 positive with 535. We just divide the type of tumor consist of three parts (ductal, lobular, and other). In tumor type obtained the most data on ductal carcinoma with 878 (63%). The difference did not achieve stastitical significance , when calculated with chi square got results >0.05. From the results can be concluded there is no relationship between Her2 with histological type and grade breast cancer.